Disparity of the language versions of the Spanish-Russian bilateral convention on judicial assistance: order of the Court of Appeal of Barcelona (12th section) number 318/2021 of 27th July - Carrillo Pozo, Luis F. (CUADERNOS DE DERECHO TRANSNACIONAL, 2022)
The Russian and Spanish versions of Article 22.1 of the 1990 Convention between the Kingdom of Spain and the Union of Soviet Socialist Republics on Mutual Assistance in Civil Matters say different things about the organization of the exequatur procedure. It is very difficult for a court to depart from the letter of the rule, of course, but the truth is that what the BOE publishes is meaningless, it is illogical. Nevertheless, there are suitable instruments in our system to reconstruct the norm and make it say what it must mean.
Keywords: exequatur; Spain-Russia bilateral convention on judicial assistance; authentic texts